2022
DOI: 10.1039/d2tc01224c
|View full text |Cite|
|
Sign up to set email alerts
|

Best practices in the measurement of circularly polarised photodetectors

Abstract: Circularly polarised light will revolutionise emerging technologies, including encrypted light-based communications, quantum computing, bioimaging and multi-channel data processing. In order to make use of these remarkable opportunities, high performance photodetectors...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 78 publications
1
16
0
1
Order By: Relevance
“…Supramolecular copolymer thin films exhibiting a strong chiral response are of considerable interest for diverse optoelectronic and photonic applications, such as OLEDs with circularly polarized luminescence (CPL), [1–5] liquid‐crystal lasers, [6] photodetectors, [7] and polarization‐dependent security features [8] . In principle, there are two approaches to obtain such chiral copolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular copolymer thin films exhibiting a strong chiral response are of considerable interest for diverse optoelectronic and photonic applications, such as OLEDs with circularly polarized luminescence (CPL), [1–5] liquid‐crystal lasers, [6] photodetectors, [7] and polarization‐dependent security features [8] . In principle, there are two approaches to obtain such chiral copolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Chiral organic π‐conjugated molecules have emerged as fascinating semiconducting materials that may be used to generate and detect light of one particular circular polarization. [ 6–10 ] Especially, non‐fullerene acceptors with excellent optical and electronic properties are considered as promising candidates for developing novel chiral functional materials. [ 11–19 ] The inherent chiroptical properties of chiral organic materials can help to simplify the design of the optical devices by eliminating the need for separate polarizers and retarders.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28–32 ] Yet, perhaps counterintuitively, opposite signs for g and g abs were found for some materials. [ 33–36 ] It was also found that g can change sign depending on the thickness of the active layer. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolekulare Copolymer‐Dünnschichten mit starker chiraler Aktivität sind von großem Interesse für verschiedene optoelektronische und photonische Anwendungen, wie OLEDs mit zirkular polarisierter Lumineszenz (CPL), [1–5] Flüssigkristall‐Laser, [6] Photodetektoren, [7] und polarisationsabhängige Sicherheitsmerkmale [8] . Prinzipiell gibt es zwei Ansätze, um solche chirale Copolymersysteme zu erhalten.…”
Section: Introductionunclassified